2021
DOI: 10.3390/ijerph18189685
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Internal and External Factors on Households’ Willingness to Sort Waste in Dammam City, Saudi Arabia

Abstract: The acceleration of growth in the population in Saudi Arabia and the increase in municipal solid waste generation have caused a problem in Dammam city: an increase in solid waste production. Therefore, solid waste sorting is an important practice of municipal solid waste management. The main objectives in this research are understanding the effect of internal and external factors on household willingness in sorting waste in Dammam city and studying the attempts to construct a theoretical research model by addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The critical role of PBC in influencing behavioural intention was reported in other TPB studies targeting households in Turkey [ 53 ], Greece [ 54 ], Saudi Arabia [ 60 ], and India [ 57 ]. Social norm was a significant predictor of intention in TPB-based studies conducted in Saudi Arabia [ 52 , 59 , 60 ] and Qatar [ 62 ]. A non-significant relationship between attitude toward recycling and intention was reported in other TPB-based studies [ 53 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical role of PBC in influencing behavioural intention was reported in other TPB studies targeting households in Turkey [ 53 ], Greece [ 54 ], Saudi Arabia [ 60 ], and India [ 57 ]. Social norm was a significant predictor of intention in TPB-based studies conducted in Saudi Arabia [ 52 , 59 , 60 ] and Qatar [ 62 ]. A non-significant relationship between attitude toward recycling and intention was reported in other TPB-based studies [ 53 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TPB has consistently shown its utility and efficacy in explaining recycling in European countries [ 42 , 43 , 44 ] and household solid waste segregation in various settings and contexts [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], including LMICs in the Eastern Mediterranean (Turkey and Greece [ 53 , 54 , 55 ]), Africa (South Africa [ 52 ] and Ghana [ 56 ]), and Asia (India [ 57 ], Iran [ 58 ], Saudi Arabia [ 59 , 60 ], and China [ 51 ]). According to Elhoushy and Lanzini’s systematic review [ 61 ], the core TPB constructs (i.e., attitude, perceived norm, and perceived behavioural control) were significantly related to behavioural intention in different contexts.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…TPB posits that the generation of environmental behavior comes from an individual’s own expectations and welfare, proposing that behavioral attitudes (BAs), subjective norms (SNs), and perceived behavioral control jointly determine an individual’s environmental behavior [ 7 ]. Currently, The TPB has consistently demonstrated its utility and efficacy in explaining recycling in European countries and domestic waste classification in various settings and contexts, including LMICs in the Eastern Mediterranean (Turkey and Greece), Africa (South Africa and Ghana), and Asia (India, Iran, Saudi Arabia, and China) [ 9 , 10 , 11 ]. Therefore, introducing the TPB into FDW classification management behavior research, from the aspects of rural residents itself, to explore the internal factors influencing the desire and behavior of its classification can improve the enthusiasm for FDW classification management.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, researchers have found that the best prediction of behavior is obtained by asking people if they intend to behave in a certain way (e.g., the Theory of Planned Behavior) [7][8][9]. Obviously, these studies follow a basic presumption: household waste separation is a self-interested behavior guided by rational choice.…”
Section: Introductionmentioning
confidence: 99%